Whistle sound recognition in a noisy environment - Lopes, Gil (2010)
This paper describes the development of an electronic system that automatically recognises the sound of a referee whistle in a nosy environment. It can be directly adapted to any robot on a robotic competition namely robotic football. Experiments have been conducted in order to test the developed system and results are shown.